2006
DOI: 10.1007/s00425-006-0366-1
|View full text |Cite
|
Sign up to set email alerts
|

A single transgene locus triggers both transcriptional and post-transcriptional silencing through double-stranded RNA production

Abstract: Silencing of a target locus by an unlinked silencing locus can result from transcription inhibition (transcriptional gene silencing; TGS) or mRNA degradation (post-transcriptional gene silencing; PTGS), owing to the production of double-stranded RNA (dsRNA) corresponding to promoter or transcribed sequences, respectively. The involvement of distinct cellular components in each process suggests that dsRNA-induced TGS and PTGS likely result from the diversiWcation of an ancient common mechanism. However, a stric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 47 publications
3
38
0
1
Order By: Relevance
“…Other siRNA classes function at the posttranscriptional level. Silencing of viral RNA and transgene transcripts involves RDR6/DCL4-dependent siRNAs (21 nucleotides) and, for at least some viruses, DCL2-dependent siRNAs (22 nucleotides) (Waterhouse et al, 2001;Xie et al, 2004;Bouche et al, 2006;Deleris et al, 2006;Fusaro et al, 2006;Waterhouse and Fusaro, 2006;Mourrain et al, 2007). Dual siRNA biogenesis pathways may be an important adaptation during antiviral defense due to the ability of viruses to suppress individual pathways (Deleris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Other siRNA classes function at the posttranscriptional level. Silencing of viral RNA and transgene transcripts involves RDR6/DCL4-dependent siRNAs (21 nucleotides) and, for at least some viruses, DCL2-dependent siRNAs (22 nucleotides) (Waterhouse et al, 2001;Xie et al, 2004;Bouche et al, 2006;Deleris et al, 2006;Fusaro et al, 2006;Waterhouse and Fusaro, 2006;Mourrain et al, 2007). Dual siRNA biogenesis pathways may be an important adaptation during antiviral defense due to the ability of viruses to suppress individual pathways (Deleris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…PTGS signals such as siRNA can be delivered over extended distances through the sieve tube (Mourrain et al 2007), usually from source to sink, following the direction of phloem flow (Tournier et al 2006). Short-distance spreading of PTGS signals via plasmodesmata is limited to within 10-15 cells (Himber et al 2003) unless the target transcript works as a template for RNA-dependent RNA polymerase 6 (RDR6), in which case the PTGS can spread through the entire plant by transitivity (Brosnan et al 2007).…”
Section: Epimutant Induction By Graftingmentioning
confidence: 99%
“…Although it has been considered that the TGS triggered by transgene-derived siRNA is not graft-transmissible (Mlotshwa et al 2002, Mourrain et al 2007), Molnar et al (2010) demonstrated that transgene-derived siRNA moved across the graft union using an Arabidopsis mutant in which siRNA biogenesis was blocked. They provided evidence that a 24-nucleotide mobile siRNA from an endogenous gene could direct epigenetic DNA methylation in the genome of the recipient cells.…”
Section: Epimutant Induction By Graftingmentioning
confidence: 99%
“…Other studies have indicated that repetitive use of the same promoter can encourage (although probably not directly trigger) transgene silencing (Mourrain et al, 2007). This observation may reflect several underlying factors, such as the presence of potential secondary structures that could interact in trans to promote de novo methylation, or the intrinsic activity of the promoters generating enough mRNA to saturate the polyadenylation machinery of the cell, allowing the formation of hairpin RNAs.…”
Section: Controlling the Expression Of Multiple Transgenesmentioning
confidence: 99%